2010
DOI: 10.2139/ssrn.1674920
|View full text |Cite
|
Sign up to set email alerts
|

Competition Effects in a Liberalized Railway Market

Abstract: This paper presents a game-theoretic model of a liberalized railway market, in which train operation and ownership of infrastructure are vertically separated. We analyze how the regulatory agency will optimally set the charges that operators have to pay to the infrastructure manager for access to the tracks and how these charges change with increased competition in the railway market. Our analysis shows that an increased number of competitors in the freight and/or passenger segment reduces prices per kilometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The same balance can be considered for passengers, especially for rail where on track capacity can be a major constraint. Lang et al (2013) showed in a game-theory model that competition in open access can increase the number of operators and consequently frequency and traffic. They argued that the regulator should incite the network manager to reduce access charges in order to increase the number of train-kilometers and decrease prices.…”
Section: Expected Results Of Competition In the Academic Literaturementioning
confidence: 99%
“…The same balance can be considered for passengers, especially for rail where on track capacity can be a major constraint. Lang et al (2013) showed in a game-theory model that competition in open access can increase the number of operators and consequently frequency and traffic. They argued that the regulator should incite the network manager to reduce access charges in order to increase the number of train-kilometers and decrease prices.…”
Section: Expected Results Of Competition In the Academic Literaturementioning
confidence: 99%
“…At the third stage, each train operator sets fare given the access charges and effective schedules. Lang et al (2013) propose a twolevel model to capture interactions among an infrastructure manager, a regulatory agency, and train operators. At the upper level, the regulatory agency sets access charge that maximizes social welfare subject to the break-even constraint for the infrastructure manager.…”
Section: Literature Review and Contributions Of The Present Studymentioning
confidence: 99%
“…Once the cost-minimum freight train schedule is obtained, we further compute 𝑇𝑀𝐶 𝑠 𝑖 𝐹 . We follow Lang et al (2013) and Kennedy (1997) by considering 𝑇𝑀𝐶 𝑠 𝑖 𝐹 to consist of fixed and variable costs. The fixed cost does not vary with train schedules, and thus does not appear in 𝐶 𝑠 𝑖 𝐹 .…”
Section: Frr's Cost 𝐶 𝑠 𝑖mentioning
confidence: 99%
“…This has led to increased demand and consumer surplus (Alexandersson and Hultén, 2008;Alexandersson et al, 2010;Lang et al, 2013;Nash et al, 2013;Mancuso, 2014). Initially, when a monopoly has been replaced by competition, significantly decreased operational costs for the operations have resulted.…”
Section: Previous Research -Experience and Expectationsmentioning
confidence: 99%